Adopting a Flipped EFL Learning Classroom in Higher Education: Knowledge and Practices - Radia Bouguebs (The Journal of Studies in Language, Culture and Society)
Higher education environments have witnessed the introduction of new pedagogies due to the wide spread of information computer technologies. The “Flipped Learning” teaching approach represents another facet of Blended Learning where the traditional and the virtual instructions are harmoniously combined in an inverted classroom.  Yet, the events that generally occur during class time occurs at home such as introducing materials, lecturing, note taking…etc, and what is intended to be completed at home as assignments and home works occurs during class session. This offers a teaching/learning environment that enhances students’ learning outcomes, and makes an efficient use of class time. Because this innovative approach has proved efficient in multiple EFL settings, developing teachers’ knowledge and practices about how to flip their EFL courses is deemed necessary. This descriptive exploratory study digs deep in Flipped learning methodology to uncover what literature has to say about the what(s), the why(s), and the how(s) of this teaching/learning approach to enable EFL teachers  overcome the major challenges that hinder the appropriate implementation of a Flipped classroom.